(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
يتناول هذا البحث دراسة تقويم فرص تطبيق مدخل إعادة هندسة العمليات لتحسين القدرة التنافسية في شركات صناعة الدواء في محافظة حلب، ويقوم هذا المدخل على إعادة التفكير الأساسي، وإعادة التصميم الجذري للعمليات للتوصل إلى تحسينات فورية في مقاييس الأداء المعروفة، ثم الانتقال إلى التفكير المبني على العمليات، والذي يتضمن تحولاً في الفكر والممارسات. وقد توصل الباحث من خلال هذا البحث، واختبار فروض البحث إلى أنه من الممكن تطبيق هذا المدخل الإداري الحديث من خلال تأييد الإدارة العليا ودعمها في الشركات محل الدراسة لهذا المدخل، ومن خلال توافر الكوادر البشرية المناسبة له، وتوافر تكنولوجيا المعلومات المتطورة، وخاصة نظم المعلومات الخاصة بالعمليات، ووجود اعتراف بضرورة تغيير النظم والأساليب المعمول بها في نظم العمليات بالشركات محل الدراسة، ومن خلال ضرورة تفهم المسؤولين والعاملين بالشركات محل الدراسة بأهمية هذا التغيير، وأن يتم إعداد نظم جديدة وتطويرها لإدارة العمليات في الشركات محل الدراسة. This study investigates the evaluation of opportunities of an application business process reengineering as an approach for improving competitiveness in pharmaceutical companies in Aleppo. This approach depends on the basic rethinking and redesign operations for achieving a direct improvement in the normal performance measurements. This approach also depends on a shift in thinking that depends on the operations, and includes a change in theory and practice. The researcher found that it is possible to apply this new managerial approach, which needs support from top management in these studied companies, through a suitable trained staff, and development information technology, especially information systems of operations. Top management and other management levels also need to believe in the necessity for a change in the existing techniques and systems in these studied companies. Therefore, the studied companies must prepare and develop new systems for operations management compatible with this suggested new approach.